Analysis of the Performance of a Solar Water Heating System Utilizing a Flat-Plate Absorber with Integrated Thermal Storage - Muhammad Anis IR; Jalaluddin Haddada; A. Amijoyo Mochtar (EPI International Journal of Engineering, 2024)
Solar water heaters (SWHs) are widely used all over the world since they use solar energy to power themselves. Solar water heaters that use aluminum-alumina (AL2O3) thermal storage at the collector base are the focus of this experimental evaluation. To maximize the efficiency of the heat transfer process and the water heating system, it is essential to incorporate thermal storage within the collector. An investigation of the efficiency of a solar water heater with AL2O3 thermal storage has been conducted. Tests are conducted on two different types of absorber plates: the standard flat-plate (SFP) collector and the SFP with AL2O3 as thermal storage. The tests are carried out over the course of a period of 180 minutes and under conditions of constant solar intensity. When the SFP and SFP-TS models are compared, the results indicate that the SFP-TS type has a greater outlet temperature than the traditional SFP. The SFP-TS model delivers a thermal efficiency boost of around 6% when compared to the SFP model with the same specifications. Adding AL2O3 to the absorber plate as a thermal storage material improves the thermal efficiency of the plate collector, increases the duration that heat is stored in the collector, and improves the absorption of radiant heat energy. Keywords: Solar Water Heater (SWH), Aluminum-alumina (AL2O3), Standard Flat Plate (SFP), Standard Flat Plate with Thermal Storage (SFP-TS)